Gelfand-Tsetlin Modules for Lie Algebras of Rank 2 (European Journal of Pure and Applied Mathematics, 2025)
We explicitly construct families of simple modules for all simple Lie algebras of rank $2$  on which a certain commutative subalgebra acts diagonally with a simple spectrum. In type $A$, these modules are the well-known generic Gelfand-Tsetlin modules.
Keywords: -Lie-algebra